Staphylococcus aureus and bovine mastitis: molecular typing of methicillinresistance and clinical description of infected quarters - OREIBY Α.; KHALIFA, H.; EID, A.; AHMED, A.; SHIMAMOTO, T.; SHIMAMOTO, T. (Journal of the Hellenic Veterinary Medical Society, 2019)
This study targeted Staphylococcus aureus (S. aureus)-mastitis of bovine as a possible source of livestock-associated methicillin-resistant Staphylococcus aureus (MRSA), to describe clinical signs of mastitis associated with MRSA and methicillin-sensitive Staphylococcus aureus (MSSA). The study area was the Gharbia and Kafrelsheikh governorates, in the central and northern regions of the Egyptian Delta. Clinical examination of animals was performed to detect clinical mastitis (CM) and clinically normal cases were tested by the California mastitis test (CMT) to identify subclinical mastitis (SCM). Accordingly, 38 mastitis cases (68 infected quarters) were detected. Milk samples were collected aseptically and were cultured on Baird Parker agar. Fifty nine Gram-positive cocci-shaped isolates were selected and preserved. In addition, 33 Staphylococcus spp. isolates originated from bovine mastitis at the same study area were obtained from Animal Health Research Institute (AHRI). The cocci-shaped Gram-positive bacteria and AHRI Staphylococcus spp. isolates were used for molecular identification of S. aureus and MRSA. Molecular screening had yielded 17 S. aureus isolates, from which five isolates (29.41%) were MRSA and 12 isolates (70.59%) were MSSA. The five MRSA isolates were mecA positive, but mecC negative. Multilocus sequence typing (MLST) of the five MRSA isolates indicated that all were sequence type 1 (ST1). S. aureus-associated cases showed different clinical forms of mastitis, including subclinical, acute, chronic, and gangrenous. However, subclinical mastitis was the only detected form associated with MRSA, which may represent a potential hidden risk for humans. Phenotypic antimicrobial-resistance pattern of MRSA isolates showed resistance to all of the tested β-lactam antimicrobials, with marked resistance to tetracycline and gentamycin. Based on our knowledge, this is the first report to identify MRSA ST1 in Egypt. Bovine mastitis could be a source for the dissemination of MRSA to humans and other animals. Additionally, while methicillin-resistance may have no effect on the clinical severity of mastitis, it does affect therapeutic success, particularly when β-lactam antimicrobials are used.